Design of Quasipolynomial-Based Controllers with Dynamical Parameters - Application to Active Vibration Damping. Issue 36 (2022) - Tliba, Sami; Boussaada, Islam; Niculescu, Silviu-Iulian; Prado, Ricardo Falcon
Abstract: In order to achieve a partial pole placement for linear time-invariant systems including time-delays in their models' representation, a method for the design of quasipolynomial-based controllers has been proposed in recent works. The ensuing controllers correspond to some output feedback control laws with constant parameters. It appears that such a controller has a limited number of degrees of freedom limiting the potential performances in closed-loop. To overcome this issue, we propose to modify the previous quasipolynomial-based controller by using dynamical parameters in their design. It turns out that the use of dynamical parameters corresponds to linear filtered terms in the control law of the original one. Such a controller is applied to the active vibration damping problem for a piezo-actuated flexible structure.